Coaching in the Special Olympics: A Comprehensive Annotated Bibliography of Resources and the Need for Continued Research in Canada - Heenan, Justin; Sumner, Sierra (International Journal of Educational Studies, 2025)
Special Olympics is a global movement dedicated to promoting inclusion and fostering a sense of community through sports for individuals with intellectual disabilities. In Canada, the organization serves over 42,000 athletes, providing lifelong athletic opportunities from childhood through adulthood. This annotated bibliography examines 34 resources on coaching in the Special Olympics, including peer-reviewed articles and grey literature with a practical focus. It highlights the ongoing nature of Special Olympics programming, which occurs weekly in communities worldwide, contrasting with the perception of it being limited to occasional Olympic events. Research underscores the benefits of Special Olympics participation, while also highlighting the need for coaching resources. Further empirical research is needed to evaluate the impact of coaching interventions and to enhance coach development and athlete experiences within the Canadian context specifically. Continued research is essential for fostering long-term success within the Special Olympics community.